2019
DOI: 10.1016/j.ajo.2019.07.021
|View full text |Cite
|
Sign up to set email alerts
|

A New Era in the Treatment of Thyroid Eye Disease

Abstract: Improved understanding of thyroid eye disease (TED) pathogenesis has facilitated identification of a targeted molecular approach for TED treatment offering the potential to halt or slow disease progression in a nonsurgical manner. Herein, we provide a summary of the current knowledge of TED management, followed by discussion of a novel insulin-like growth factor-1 receptor (IGF-1R) antagonist antibody and its potential to change the course of the disease.DESIGN: Perspective. METHODS: Review of the literature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 45 publications
0
47
0
1
Order By: Relevance
“…There was a significant difference in proptosis reduction between the teprotumumab group and the placebo group at weeks 6, 12, 18, and 24. Data from secondary endpoints are yet to be presented at the time of this review [56,57].…”
Section: Teprotumumabmentioning
confidence: 99%
“…There was a significant difference in proptosis reduction between the teprotumumab group and the placebo group at weeks 6, 12, 18, and 24. Data from secondary endpoints are yet to be presented at the time of this review [56,57].…”
Section: Teprotumumabmentioning
confidence: 99%
“…A landmark breakthrough is the introduction of specific IGF-1R blocker teprotumumab. [ 6 22 23 ] It has been demonstrated that eight infusions of teprotumumab over 24 weeks were associated with clinical improvement in patients with moderate-to-severe, active TED, shown by reductions in CAS, proptosis, subjective diplopia, and improved quality of life. [ 22 ] The reduction in proptosis was comparable to orbital decompression.…”
Section: Newer Trendsmentioning
confidence: 99%
“…The biphasic natural history of TED as described over six decades ago by Francis Rundle[ 6 7 ] has an initial active, inflammatory, progressive component, followed by a static, noninflammatory, fibrotic sequelae. [ 8 9 ] The clinical course, however, is heterogenous with numerous permutations of severity and duration of inflammation and functional derangement.…”
mentioning
confidence: 99%
“…3,10,14 However, no treatments have been shown to prevent or reverse the underlying tissue changes in TED. 15 When surgery is indicated, orbital decompression is typically performed first, then strabismus surgery and eyelid retraction considered last, as each preceding procedure may influence the appearance and outcome of the following operation. 16,17 Thyroid diseases have several implications for anaesthetists.…”
Section: Thyroid Eye Disease: Clinical Features and Treatment Optionsmentioning
confidence: 99%